Facile design of oxide‐derived Cu nanosheet electrocatalyst for CO2 reduction reaction. Issue 5 (16th February 2023) - Jang, Juhee; Zhu, Shangqian; Delmo, Ernest Pahuyo; Li, Tiehuai; Zhao, Qinglan; Wang, Yinuo; Zhang, Lili; Huang, Hongwen; Ge, Jingjie; Shao, Minhua
Abstract: Despite of superior performance of the oxide‐derived copper (OD‐Cu) in producing valuable hydrocarbons during CO2 RR, its fabrication process is still ambiguous and complicated. In this work, we develop a simple microwave‐assisted method to synthesize the oxide‐derived Cu nanosheet (OD‐Cu NS) and reveal that the oxidation state of Cu species is controlled by varying the Cu precursor amount. Notably, the simultaneous formation of nano‐sized Cu domains influence the surface roughness of OD‐Cu NS. The partially oxidized Cu surface exhibits a superior faradaic efficiency (FE) of C2+ products up to 72%, along with a partial current density of 55 mA cm −2 in a neutral KHCO3 solution. More importantly, the as‐obtained OD‐Cu NS shows a synergetic effect on dissociating of CO2 molecules by the strong binding energy and promoting of C2+ compounds productivity by the enlarged electrochemical surface area. This work provides a new insight for designing efficient OD‐Cu catalysts toward CO2 RR. Abstract : An oxide‐derived Cu nanosheet with rough and partially oxidized surface is prepared by using simple microwave‐assisted method. Based on the fabricated Cu nanosheets, the FE C 2 + can reach up to 72% with the partial C2+ current density of 55 mA cm −2 in CO2 RR, ascribing to the increase of ECSA and strong interaction with the dissociated CO2 .